Curcumin-Loaded Mesoporous Silica Nanoparticles Dispersed in Thermo-Responsive Hydrogel as Potential Alzheimer Disease Therapy - Ribeiro, Tais de Cassia [UNESP]; Sábio, Rafael Miguel [UNESP]; Luiz, Marcela Tavares [UNESP]; de Souza, Lucas Canto [UNESP]; Fonseca-Santos, Bruno; Cides da Silva, Luis Carlos; Fantini, Márcia Carvalho de Abreu; Planeta, Cleopatra da Silva [UNESP]; Chorilli, Marlus [UNESP] (MDPI, 2022)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by cognitive and behavioral impairment. Curcumin-loaded mesoporous silica nanoparticles (MSN-CCM) can overcome the drawbacks related to the free curcumin (CCM) clinical application, such as water insolubility and low bioavailability, besides acting over the main causes associated to AD. A thermo-responsive hydrogel is an interesting approach for facilitating the administration of the nanosystem via a nasal route, as well as for overcoming mucociliary clearance mechanisms. In light of this, MSN-CCM were dispersed in the hydrogel and evaluated through in vitro and in vivo assays. The MSNs and MSN-CCM were successfully characterized by physicochemical analysis and a high value of the CCM encapsulation efficiency (EE%, 87.70 ± 0.05) was achieved. The designed thermo-responsive hydrogel (HG) was characterized by rheology, texture profile analysis, and ex vivo mucoadhesion, showing excellent mechanical and mucoadhesive properties. Ex vivo permeation studies of MSN-CCM and HG@MSN-CCM showed high permeation values (12.46 ± 1.08 and 28.40 ± 1.88 μg cm−2 of CCM, respectively) in porcine nasal mucosa. In vivo studies performed in a streptozotocin-induced AD model confirmed that HG@MSN-CCM reverted the cognitive deficit in mice, acting as a potential formulation in the treatment of AD.
Keywords: brain disorders; curcuminoids; drug delivery systems; mesoporous silica nanoparticles; neurodegenerative disorder